Successful Deer Management in Scotland Requires Less Conflict Not More - Kirkland, Hannah; Hare, Darragh; Daniels, Mike; Krofel, Miha; Rao, Shaila; Chapman, Tatiana; Blossey, Bernd (Frontiers in Conservation Science, 2021)
What would successful deer management look like in Scotland? To some, flourishing populations of native wild deer represent success. But to others, negative impacts such as damage to woodlands and peatlands, agricultural and forestry losses, deer-vehicle collisions, and facilitating Lyme disease spread represent failure. Conflicting interests and incentives among people involved in deer management mean a common definition of success, and therefore clear management targets, remain elusive. While some environmental groups urgently call for an increase in the number of deer culled (shot) each year, other stakeholders aim to maximise deer numbers. Overcoming this governance failure will require clearly articulated, scientifically valid, and socially acceptable socio-ecological objectives to be co-produced by a broad range of stakeholders. Systematic monitoring of deer impacts will also be needed to evaluate the ability of specific management interventions to achieve defined objectives. Reintroducing Eurasian lynx (Lynx lynx) has been suggested as a means to reduce deer numbers and their negative ecological and socioeconomic impacts. However, evidence of lynx impacts on deer numbers, deer impacts, and social conflicts over deer suggest lynx reintroduction alone would not effectively reduce negative impacts of deer in Scotland, though it could be part of a broader solution. In the short-term, achieving sustainable numbers of deer in Scotland will require a substantial increase in the number of deer culled and effective changes to the way deer management is incentivised, regulated, implemented, and monitored.